Um estudo sobre as propostas de comunicação da central de atendimento ao turista – cat para o desenvolvimento da atividade turística no município de arraias tocantins - Costa, Júnior Castro (Universidade Federal do Tocantins, 2021)
The objective of this work is to discuss the relationship between tourism and new forms of communication as a tool for dissemination of tourism activity in the municipality of Arraias, based on the implementation of the Tourist Assistance Center - CAT in the dependencies of the Historical and Cultural Museum of Arraias - MHCA. For this, there are discussions about tourism and receptive tourism, a theme much discussed, mainly due to its potential in terms of economic growth and local income generation. Qualitative, descriptive researches and secondary data collection were carried out in order to understand the tourist dynamics in Arraias / TO. In the course of the research it was possible to perceive that the use of several communication tools, especially social networks, served to strengthen the tourist information in Arraias and as a consequence the dissemination of the culture and the potential tourist attractions of the municipality with a high reach in a short time, and that if this destination consolidates, CAT will already have a wide range of users, given the signature of the technological era. In addition, the virtual support that the center can offer for people who wish to visit the city is a fundamental element for the development of tourism in the municipality. The paper also presents other communication tools developed within the scope of the academic internship at MHCA. These initiatives, which are seen as lasting policies, will notably favor the deployment of tourism, serving as a starting point for the development of this sector in Arraias.